Educational videos as an interactive component of training at the department of pediatrics, neonatology and childhood infections of Donetsk National Medical University - I.V. Balychevtseva; І.G. Samoylenko; O.Ye. Chernyshova; V.V. Kryvosheieva; M.V. Karpovich; T.R. Polеsova; Yu.V. Zhihal; E.M. Pavlov; V.V. Gerasymenko (Zaslavsky O.Yu., 2018)
The search and implementation of innovative methods of education are performed, as well as their mastering and using on practice in order to improve the quality of learning by students. These methods include not only the ways of education system formation but also content, forms, methods, and means of pedagogy. The possible use of computer innovations in pedagogy is being improved and becomes more interesting, diverse, and available which is the decisive criterion for their widespread application in practice. Interactive methods using videofilms in the educational process are actively applied in order to improve the quality of learning by students and interns of all training courses at the department of pediatrics, neonatology and childhood infections of Donetsk National Medical University.